A Virus-Induced Assay for Functional Dissection and Analysis of Monocot and Dicot Flowering Time Genes . Issue 2 (11th April 2017) - Qin, Cheng; Chen, Weiwei; Shen, Jiajia; Cheng, Linming; Akande, Femi; Zhang, Ke; Yuan, Chen; Li, Chunyang; Zhang, Pengcheng; Shi, Nongnong; Cheng, Qi; Liu, Yule; et al.
Abstract : A PVX-based VIF assay was designed in order to identify amino acids in the FT protein that are essential for flowering and to examine floral induction by mono- and dicotyledonous FT genes. Abstract: Virus-induced flowering (VIF ) uses virus vectors to express Flowering Locus T ( FT ) to induce flowering in plants. This approach has recently attracted wide interest for its practical applications in accelerating breeding in crops and woody fruit trees. However, the insight into VIF and its potential as a powerful tool for dissecting florigenic proteins remained to be elucidated. Here, we describe the mechanism and further applications of Potato virus X (PVX)-based VIF in the short-day Nicotiana tabacum cultivar Maryland Mammoth. Ectopic delivery of Arabidopsis ( Arabidopsis thaliana ) AtFT by PVX/AtFT did not induce the expression of the endogenous FT ortholog NtFT4 ; however, it was sufficient to trigger flowering in Maryland Mammoth plants grown under noninductive long-day conditions. Infected tobacco plants developed no systemic symptoms, and the PVX-based VIF did not cause transgenerational flowering. We showed that the PVX-based VIF is a much more rapid method to examine the impacts of single amino acid mutations on AtFT for floral induction than making individual transgenic Arabidopsis lines for each mutation. We also used the PVX-based VIF to demonstrate that adding a His- or FLAG-tag to the N or C terminus of AtFT could affect its florigenic activity and that this system can be applied to assay the function of FT genes from heterologous species, including tomato ( Solanum lycopersicum ) SFT and rice ( Oryza sativa ) Hd3a . Thus, the PVX-based VIF represents a simple and efficient system to identify individual amino acids that are essential for FT-mediated floral induction and to test the ability of mono- and dicotyledonous FT genes and FT fusion proteins to induce flowering.